2016
DOI: 10.4269/ajtmh.16-0086
|View full text |Cite
|
Sign up to set email alerts
|

Scrub Typhus in a Tertiary Care Hospital in North India

Abstract: Abstract. Scrub typhus, a zoonotic disease caused by the bacterium Orientia tsutsugamushi, has become endemic in many parts of India. We studied the clinical profile of this infection in 228 patients that reported to this tertiary care center from July 2013 to December 2014. The median age of patients was 35 years (interquartile range = 24.5-48.5 years), and 111 were males and 117 females. A high-grade fever occurred in 85%, breathlessness in 42%, jaundice in 32%, abdominal pain in 28%, renal failure in 11%, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 32 publications
6
60
2
Order By: Relevance
“…The male-to-female ratio was 1.4:1 in our study which is similar to other studies from South India. [ 14 15 16 17 18 19 ] A similar male preponderance has also been seen in other studies from the Asia-Pacific region outside India except South Korea (male-to-female ratio of 1:1.6), a trend that may be influenced by the prevailing socioeconomic culture of females occupied with farming. [ 20 21 22 23 24 ]…”
Section: Discussionsupporting
confidence: 63%
“…The male-to-female ratio was 1.4:1 in our study which is similar to other studies from South India. [ 14 15 16 17 18 19 ] A similar male preponderance has also been seen in other studies from the Asia-Pacific region outside India except South Korea (male-to-female ratio of 1:1.6), a trend that may be influenced by the prevailing socioeconomic culture of females occupied with farming. [ 20 21 22 23 24 ]…”
Section: Discussionsupporting
confidence: 63%
“…(16) Classically known as a post monsoon disease, this seasonal occurrence of scrub typhus was a prolonged one, extending well into the month of December. (17) During our study also period of highest incidence was found to be in post monsoon season (August to November). Eschar at the site of attachment of the larval mite/chigger is considered highly suggestive of scrub typhus, but occurs in a variable proportion of patients in different studies.…”
Section: Discussionsupporting
confidence: 62%
“…Fever of >12 days, presence of eschar, ICU admission, shock needing ionotropes, CNS dysfunction etc. have also been proven to be predictors of mortality [ 5 , 14 , 35 ]. These give valuable hints to the impending fatal outcome and may help the clinicians to initiate the intensive management.…”
Section: Discussionmentioning
confidence: 99%